We carry the sea in our hands : a novel - Kim, Janie (Alcove Press, 2024)
"Abby Rodier was a "drop-box baby," a Korean orphan whose mother could not take care of her and left her as an infant. Abby's tumultuous experience in the American foster care system has led her to live a solitary and guarded life, closed off to almost everyone except her best friend Iseul, whose parents took Abby into their home as a child. Abby's work studying the origins of life in sea slugs and bacteria leads her to wonder about her birth parents and question her place in this world. It's not long before Abby stumbles upon a biological discovery that will change the course of her life. Meanwhile, Iseul's devotion to their ill brother leads to an entanglement between her work as an investigative journalist and the murky world of black-market medicine. After a tragic event, Abby's life is thrown into a tailspin. With the rug pulled from under her feet, she spirals into a disorientation of grief, apparitions, and compulsions. With the help of those around her, Abby must embark on a journey to understand her true roots and make peace with her present." -- Jacket flap